Spiritual capital : wealth we can live by - Zohar, Danah, 1945- (Berrett-Koehler, 2004)
Spiritual Capital presents a new vision of capitalist society that transcends the greed, materialism, and meaninglessness so rampant today. It offers an idea of wealth, profit, and capital that's about more than simply money.